Effectiveness of neurokinetic therapy on pain and plantar fascia thickness among patients with plantar fasciitis - Prajan, Preethi Shri; Abathsagayam, Kumaresan; Vishnuram, Surya (Journal of the Foot & Ankle, 2024)
Objectives: Identify the effectiveness of neurokinetic therapy on pain and plantar fascia thickness in patients with plantar fasciitis. Method: An experimental study was performed on 80 patients with plantar fasciitis after screening based on selection criteria. The patients were randomly allocated into two groups: the neurokinetic therapy group (n = 40) and the foot core exercises group (n = 40). In both groups, the treatments were given for two weeks, five days each week. The pre-and post-test results were assessed. A statistical analysis was performed on the gathered data. Result: A significant statistical difference was observed between the groups; the post-test mean value of the Foot Function Index scale in the neurokinetic therapy group was 129.12, while in the foot core exercises group was 141.42. Additionally, the post-test mean value of the therapeutic ultrasound in the neurokinetic therapy group was 3, whereas in the foot core exercises group was 3.38. These values yielded a p-value of less than 0.001. Conclusion: This study demonstrated an improvement in both groups. However, the neurokinetic therapy group showed a significant improvement in pain, functionality, and plantar fascia thickness compared to the foot core exercises group. Level of evidence IV; Experimental study.